Chemically robust solution-processed indium zinc oxide thin film transistors fabricated by back channel wet-etched Mo electrodes. Issue 58 (1st June 2016) - Kim, Da Eun; Cho, Sung Woon; Kim, Bora; Shin, Jae Hui; Kang, Won Jun; Yun, Myeong Gu; Beak, Seung Ki; Cho, Hyung Koun; Kim, Yong-Hoon; Kim, Yunseok
Abstract : We designed a systematic strategy for a chemically robust solution-processed IZO thin film transistor with back channel wet-etched Mo electrodes, which showed superior electrical performance and uniformity. Abstract : We designed a systematic processing strategy for solution-processed indium zinc oxide thin film transistors (TFTs) with chemically wet-etched Mo electrodes and chemically durable channels prepared by a sol–gel method. First, we explored the effect of H2 O2 wet-etchant pH to define efficiently wet-etched Mo source/drain electrodes without Mo residues and with minimal chemical damage to the indium zinc oxide (IZO) channel. Next, sufficient condensation reaction times and a two-step engineering process were performed on the solution-processed IZO thin films to improve their inferior chemical durability (from incomplete metal oxygen bonds and low film density). The solution-processed IZO channels with wet chemical patterning and superior chemical durability preserved the original electrical transfer properties with minimal electrical degradation in the back channel etch (BCE) processes. Finally, additional N2 post-annealing partially recovered the field-effect mobility (2.5 cm 2 V −1 s −1 ), and on-current without oxidation of the Mo electrode, comparable to the lift-off processed TFTs. This approach provides a significant potential for using wet-based BCE processes in sol–gel prepared oxide TFTs.